CREATION AND DELIVERY OF EDUCATIONAL VIDEO CONTENT: BUSINESS PROCESS MODELING, CRITERIA, QUALITY EVALUATION INDICATORS - Korolchuk, Valentyna; Saiapina, Taisiia; Voloshyna, Tetiana (Physical and Mathematical Education, 2023)
Formulation of the problem. The increasing importance of creating and delivering video content in the educational process, as well as the need to ensure the quality, accessibility, and effectiveness of education, encompasses several aspects, including the production of high-quality video content, storage, and efficient delivery to educational learners. Solving this problem can enhance the quality of education and provide better access to diverse educational content for different levels and learning styles.Materials and Methods. A business model was developed in order to solve the problem. The analysis, classification, and systematization of scientific sources and the expert evaluation method were applied to evaluate the quality of educational video content according to the specified criteria (balanced and relevant content, personalization, interactivity, accessibility, evaluation) and relevant indicators.Results. The study involved analyzing the effectiveness of video in the educational process. A business process model has been developed that allows the teacher/ author and administrator to create, store, and deliver educational video content to students. Criteria and relevant indicators for video quality assessment have been determined, and expert evaluation has been carried out. The article summarizes the results of pedagogical research with the participation of expert students of the Master of Science who studied in the specialty 011 Educational, pedagogical sciences of the educational program "Information and communication technologies in education" (full-time and part-time forms of study), and teachers who have experience in creating and delivering educational video content during blended and distance learning. The influence of criteria and indicators on the quality of the video, according to the opinion of two groups of experts, students and teachers, was determined.Conclusions. The developed business model and defined criteria and indicators for evaluating the quality of video content will contribute to increasing the quality of educational services. The proposed business process model can be used in creating and delivering educational content to education seekers, as well as in the framework of improving the qualifications of teachers in institutions of various levels of education. During the creation and delivery of educational content, it is recommended to consider criteria and indicators for evaluating the quality of educational video content according to the proposed business model.
Keywords: business process modeling; educational video content; creating video content; delivery of video content; evaluation criteria and indicators